Evaluation of a Comprehensive Assessment-Based Intervention for Secondary Students With Social, Emotional, and Behavioral Problems. (March 2021) - Kern, Lee; Evans, Steven W.; Lewis, Timothy J.; State, Talida M.; Mehta, Paras D.; Weist, Mark D.; Wills, Howard P.; Gage, Nicholas A.
Despite a high dropout rate and poor educational and posteducational outcomes, limited evidence-based practices have been validated with students at the high school level who have emotional and behavioral problems. The purpose of this study was to evaluate the impact of a multitreatment, assessment-based intervention package. Participants were 647 high-school-age students with both emotional/behavioral problems and impairment in school functioning. Using a randomized controlled trial, the intervention group showed significantly fewer disruptions, measured using direct observation. No significant differences were found in directly observed engagement or on standardized measures. However, in general, interventions were implemented with low frequency. Dosage effects were examined for classroom interventions and a social skills intervention (Interpersonal Skills Group [ISG]). Results indicated a dosage effect for ISG, reflected in standardized measures. Although implementation was low, teachers and staff rated practices that they implemented highly favorably.